Enlarged brain perivascular spaces correlate with blood plasma osmolality in the healthy population: A longitudinal study - Morozova, Alexandra; Španiel, Filip; Škoch, Antonín; Brabec, Marek; Zolotarov, Grygoriy; Musil, Vladimir; Zach, Petr (NeuroImage, 2024)
Enlarged perivascular spaces (EPVS) are increasingly recognized as an MRI detectable feature of neuroinflammatory processes and age-related neurodegenerative changes. Understanding perivascular characteristics in healthy individuals is crucial for their applicability as a reference for pathological changes. Limited data exists on the EPVS load and interhemispheric asymmetry in distribution among young healthy subjects. Despite the known impact of hydration on brain morphometric studies, blood plasma osmolality's effect on EPVS remains unexplored. This study investigated the influence of age, total intracranial volume (TIV), and blood plasma osmolality on EPVS characteristics in 59 healthy adults, each undergoing MRI and osmolality assessment twice within 14.8 months (mean ± 4 months). EPVS analysis was conducted in the centrum semiovale using high-resolution automated segmentation, followed by an optimization algorithm to enhance EPVS segmentation accuracy. Linear Mixed Effects model was used for the statistical analysis, which unveiled significant inter-individual variability in EPVS load and inter-hemispheric asymmetry. EPVS volume increased with age, higher TIV and lower blood plasma osmolality levels. Our findings offer valuable insights into EPVS characteristics among the healthy population, establishing a foundation to further explore age-related and pathological changes.
Keywords: senioři; osmolární koncentrace; longitudinální studie; Middle Aged; mužské pohlaví; mozek; Adult; mladý dospělý; Osmolar Concentration; Glymphatic System; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Brain; Young Adult; ženské pohlaví; Humans; lidé středního věku; glymfatický systém; Longitudinal Studies; dospělí; Female; Aged; lidé; Male